The expository phase of debriefing in clinical simulation: a qualitative study - Giulio Fenzi; Carolina Alemán-Jiménez; Pedro Simón Cayuela-Fuentes; Gabriel Segura-López; Cesar Leal-Costa; José Luis Díaz-Agea (BMC Nursing)
Abstract Background Clinical simulation fosters reflective, experiential learning in a safe environment, allowing participants to learn from mistakes without patient risk. Debriefing, essential for reflection, is typically facilitator driven. The MAES© methodology (Self-Learning Methodology in Simulated Environments) shifts the focus to students, guiding them through six sequential phases: group identity creation, topic selection, objective setting, competency establishment, scenario design, simulation, and debriefing. MAES© introduces an expository phase in debriefing, where students present theoretical and practical content. The facilitator assumes a significant, yet secondary role, fostering increased student-led learning opportunities and, at times, enabling even trained real patients to co-facilitate the debriefing. Objective To explore participants’ experiences and perceptions regarding the expository phase of debriefing within the MAES© methodology framework, with specific focus on the student-led debriefing component. Method A descriptive qualitative inductive approach with thematic content analysis was used. Open-ended questionnaires from 151 undergraduate final year and post-graduate nursing students, captured their experiences with the MAES© expository phase. Open-ended questionnaires allow participants to freely and anonymously express their perspectives and experiences. Responses were transcribed, independently coded, and analyzed using MaxQDA® v18. Data were coded and analyzed based on absolute and relative frequencies of emerging categories. The study adhered to the SRQR (Standards for Reporting Qualitative Research) guidelines. Results The analysis revealed several key themes in student evaluations. Satisfaction with the methodology emerged strongly, with over one-third of participants expressing no desired changes. The reflective nature of the approach was prominently valued, along with its effectiveness for concept clarification and fostering collaborative learning. Participants particularly noted developmental outcomes in communication competencies and technical skills, while appreciating the motivational learning environment and evidence-based focus. The suggested improvements focused on three main aspects: increased session dynamism, a greater use of visual and interactive elements, and reduced dependence on slide-based presentations. Conclusion The study highlights the value of the expository phase in the MAES© methodology, emphasizing its effectiveness in clarifying concepts, fostering collaboration, and developing technical and communication skills. It also promotes student autonomy through active engagement. However, participants suggested improvements, such as greater dynamism, personalization, and varied presentation methods using videos, skill stations or patient’s-oriented debriefing. Overall, the expository phase proves to be a valuable pedagogical tool with potential for broader application in simulation-based learning and other debriefing models. Clinical trial number Not applicable.